Cytotoxic effects of parijoto (Medinilla speciosa Reinw. Ex. Bl.) methanol extract combined with cisplatin on WiDr colon cancer cells through apoptosis induction - Anif Nur Artanti; Fea Prihapsara; Ranita Kumalasari Susanto (Universitas Gadjah Mada, 2022)
Parijoto (Medinilla speciosa Reinw. Ex. Bl.) is a medicinal plant with cytotoxic effects on cancer cells in vitro. As only a limited number of studies have reported the effect of parijoto on colon cancer cells, this study initially aimed to measure the total flavonoid levels and potential cytotoxic effects of parijoto methanol extract (PME) through cell viability assays and expression of the apoptotic protein on WiDr colon cancer cells as a model. PME cytotoxic activity was determined by conducting a cytotoxicity test on WiDr colon cancer cells using the MTT assay. The synergistic cytotoxic effects of the PME and cisplatin were tested to obtain the combination index (CI) value. Apoptosis was analyzed by flow cytometry, and the apoptotic protein expression was observed by immunocytochemical tests. Furthermore, quercetin as a major flavonoid in PME was measured using a UV–Vis spectrophotometer. The results showed that PME had a moderate cytotoxic activity with an IC50 of 198.64±1.6 µg/mL, whereas the IC50 of cisplatin was 2.34±0.7 µg/mL. The PME with cisplatin combination test showed a strong synergistic effect with a CI value of <1 (0.1‐0.4). The combination showed increased apoptosis properties compared to PME treatment alone. In addition, immunocytochemistry showed that PME alone or in combination with cisplatin increased the pro‐apoptosis proteins (p53 and caspase‐9) and suppressed Bcl‐2 expression. Moreover, the cell viability value increased as the PME concentration decreased. The administration of PME led to changes in cell morphology, lower cell density, and a decreasing number of living cells. Therefore, the combination of PME and cisplatin had a strong synergistic effect in inducing apoptosis.